ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT KELURAHAN GIRIROTO KOTA BOYOLALI - Enggar Priska; Affan Nurhaq; Maya Widyana Dewi (ITB AAS INDONESIA, 2024)
This research aims to determine the effect of service quality on community satisfaction at the Giriroto Village Office, Boyolali City. The data analysis method used in this research is Simple Regression Analysis, t test, coefficient of determination test (R2) using the SPSS application version 23 32 bytes. Based on simple linear regression analysis, it shows that the higher the quality of service, the more influential or significant it will be on the satisfaction of the people of Giriroto Village. The coefficient value shows that service quality and community satisfaction have a positive effect. Thus, the better the quality of service provided by the employees of the Giriroto Subdistrict Office, Boyolali City, the more community satisfaction will increase. Meanwhile, based on the partial test (t), which means that partially the service quality variable has a significant effect on community satisfaction. And the Determination coefficient test obtained an Adjusted R Square value of 0.708, which means the influence of the independent variable (service quality) on the dependent variable (community satisfaction) was 70.8% while the remaining 29.2% was influenced by other variables not examined in this research.